Pengaruh Kebijakan Pengalihan Subsidi Bahan Bakar Minyak (BBM) untuk Pendidikan Anak-Anak di Rumah Tangga Miskin - Pratikto, Adji (Jurnal Ekonomi Kuantitatif Terapan, 2018)
Education is one of the most important aspects in a person's life because it will affect his life for the better in the future. They will have the opportunity to get a better job, better marriage and so on. However, in developing countries, poverty is still one of the factors that prevent poor households from accessing education for their children. Therefore, it is necessary for the government to provide accessible education by poor households. One obstacle for governments to provide educational services is the cost of providing them. Therefore, in this research will be simulated the transfer of fuel subsidy for the provision of education services using the SUBSIM analysis tool. Based on the scenario built, it was found that the most enjoying the price of education services decline was the poor households with the highest 20% per capita consumption expenditure. They had higher education expenditure compared to other households. Therefore, the challenge of the government is how to encourage poor households to  send their children for higher education